Ganho de peso e alterações anatomopatológicas de tilápia-do-nilo arraçoadas com farelo de cacau - Pezzato, Luiz Edivaldo [UNESP]; De Oliveira, Ana Cristina Belarmino [UNESP]; Dias, Edméa [UNESP]; Barros, Margarida Maria; Pezzato, Antonio Celso [UNESP] (My University, 1996)
The experiment was carried out on the Laboratory of Fish Nutrition - F.M.V.Z., Campus Botucatu - integrated to the UNESP Aquaculture Center, with the main purpose of evaluating the effects of the use of cocoa meal (Theobroma cacao) on diets for Nile tilapia (Oreochromis niloticus) fingerlings. Six diets with increasing levels of cocoa meal (CM): 0% CM; 4% CM; 8% CM; 12% CM; 16% CM and 20% CM were fed for 120 days to the fingerlings, in a completely randomized design. Results showed no significant adverse effect of cocoa meal on weight gain (p>0.05), but there were restrictions to its use on diet, as it was found pathological effects on liver and also behavior disturbs caused by alkaloids present on the product.
Weight gain and anatomopathological disturbs on nile tilapia fed with cocoa meal
Keywords: Alkaloids; Aquaculture; Diet; Feeding